CONVERSATION TRAINING FOR STUDENTS OF SMAN 1 PAITON THROUGH ZOOM MEETINGS - Tirmidi Tirmidi; Firlia Nurul Anisa; Mar’ah Zamratin Fuadah; Ifa Aprilia Fabela; Farihatul Qamariyah; Siti Nur Diana (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
The ability to communicate in English is an important skill in this global age. However, students at SMAN 1 Paiton still face challenges in pronunciation and have limited English vocabulary. One reason for this is the lack of daily practice in speaking English. This training program is designed to improve English speaking skills in an appropriate manner using the Zoom Meeting conversation method. The program includes training sessions covering both theoretical and practical aspects. The training will be conducted in six sessions, each lasting 30 minutes. Evaluation will be conducted through short presentations. It is hoped that this program will contribute positively to improving the speaking skills of high school students.